Comparison of selected view creation technologies in applications using the Laravel framework - Woś, Albert; Pańczyk, Beata (Journal of Computer Sciences Institute, 2021)
This article presents the result of a comparison of selected view creation technologies in applications using the Laravel framework. Using the multi-criteria analytic hierarchy process (AHP) method the most efficient template system was selected from Blade, Twig, and Smarty. Presented template systems were used with Laravel framework to create a landing page on the basis of which the experiment was conducted.